DAKWAH DAN TANTANGAN ETIKA GLOBAL - Rosdislena Rosdialena (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Da'wah that develops at this time has a tendency to doctrine, where the community is likened to a piggy bank that must continue to be filled with a set of beliefs and moral values in his life. One of the most important issues is the challenge of da'wah in the global era as the impact of the globalization process related to the religious life of the community, namely the depletion of the space of religiosity in the context of human life. On the same side, we can see that some Muslims tend to accept what comes from the West without filtering it out. Besides that, the challenge of global ethics that needs to be a very important study at this time is the dissemination of perspectives around human relations with the natural environment, family relationships, social harmony, especially those that develop in developed countries. For this reason, da'wah in the global era requires the dai to be better able to adjust to the times.